Analysis of major bile acids in saliva samples of patients with Barrett's esophagus using high-performance liquid chromatography-electrospray ionization-mass spectrometry - Ďurč, Pavol; Dosedělová, Věra; Foret, František; Dolina, Jiří; Konečný, Štefan; Himmelsbach, Markus; Buchberger, Wolfgang; Kubáň, Petr (Journal of chromatography. A, Including electrophoresis and other separation methods, 2020)
A fast, non-invasive, high-performance liquid chromatographic screening method with electrospray ionization mass spectrometric detection was developed for the analysis of three major glycine-conjugated bile acids in human saliva. Using a mobile phase composed of 80% methanol and 0.1% formic acid, glycocholic, glycodeoxycholic, and glycochenodeoxycholic acids were separated in less than 4 minutes with sensitivity in the low nM range. Bile acids are thought to contribute to the pathology of various complications in gastroesophageal reflux disease, for instance, Barrett's esophagus, which may eventually lead to esophageal carcinoma. In this pilot study, samples of saliva obtained from 15 patients with Barrett's esophagus of various severities were compared to saliva samples from 10 healthy volunteers. Glycochenodeoxycholic acid was significantly elevated in the patients and principal component analysis of all bile acids could distinguish the most severe Barrett's esophagus patients. We also reported on the detection of glycochenodeoxycholic acid in exhaled breath condensate for the first time. The promising results of this pilot study warrant future investigation, aiming at non-invasive diagnostics of Barrett's esophagus susceptibility in patients with gastroesophageal reflux disease.
Keywords: analýza hlavních komponent; Chromatography, High Pressure Liquid; Signal Processing, Computer-Assisted; Bile Acids and Salts; Humans; referenční standardy; lidé středního věku; žlučové kyseliny a soli; Female; dospělí; Barrettův syndrom; počítačové zpracování signálu; lidé; Principal Component Analysis; pilotní projekty; reprodukovatelnost výsledků; Pilot Projects; Reference Standards; Saliva; hmotnostní spektrometrie s elektrosprejovou ionizací; Adult; ženské pohlaví; Barrett Esophagus; Male; Middle Aged; Reproducibility of Results; sliny; Spectrometry, Mass, Electrospray Ionization; mužské pohlaví; vysokoúčinná kapalinová chromatografie